2011
DOI: 10.1002/14651858.cd005184.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Creatine and creatine analogues in hypertension and cardiovascular disease

Abstract: Background The creatine kinase system, the central regulatory system of cellular energy metabolism, provides ATP in situ at ATP-ases involved in ion transport and muscle contraction. Furthermore, the enzyme system provides relative protection from tissue ischaemia and acidosis. The system could therefore be a target for pharmacologic intervention. Objectives To systematically evaluate evidence regarding the effectiveness of interventions directly targeting the creatine kinase system as compared to placebo cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 9 publications
0
18
0
1
Order By: Relevance
“…We screened 493 reviews after removal of duplicates. Based on their titles and abstracts, a total of 82 reviews met the inclusion criteria and made up the data set 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 65 66 67 68 69 70 71 72 73 74 75 76 77 78 79 80 81 82 83 84 85 86 87 88 89 90 91 92 93 94 95 96 97 . The 82 relevant CSRs included 1177 RCTs.…”
Section: Resultsmentioning
confidence: 99%
“…We screened 493 reviews after removal of duplicates. Based on their titles and abstracts, a total of 82 reviews met the inclusion criteria and made up the data set 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 65 66 67 68 69 70 71 72 73 74 75 76 77 78 79 80 81 82 83 84 85 86 87 88 89 90 91 92 93 94 95 96 97 . The 82 relevant CSRs included 1177 RCTs.…”
Section: Resultsmentioning
confidence: 99%
“…In animal studies it has been demonstrated that inhibition of the CK system leads to a shift from type II to type I fiber predominance, with mitochondrial proliferation and increased oxidative phosphorylation, weight loss, and increased insulin sensitivity . However, a recent review evaluating existing therapeutic strategies that target the CK system in hypertension and cardiovascular diseases was inconclusive . Given the heterogeneity and small sample size of the trials, the authors stated that larger clinical studies are needed to confirm these observations.…”
Section: Discussionmentioning
confidence: 99%
“…[30][31][32] However, a recent review evaluating existing therapeutic strategies that target the CK system in hypertension and cardiovascular diseases was inconclusive. 33 Given the heterogeneity and small sample size of the trials, the authors stated that larger clinical studies are needed to confirm these observations.…”
Section: Discussionmentioning
confidence: 99%
“…However, our finding is consistent with no reported blood pressure effect in three published male only placebo-controlled trials with creatine [ 160 , 161 , 162 ] and one mix-sex study [ 144 ]. There has been one systematic review on the use of creatine and creatine analogues in hypertension and cardiovascular disease, which also concluded no change in blood pressure with creatine supplementation in myocardial infarction or heart failure trials [ 163 ]. Overall, more thorough investigations are required to definitively rule in or out adverse cardiovascular effects of creatine supplementation in both male and female populations.…”
Section: Discussionmentioning
confidence: 99%